Phosphorus in forest ecosystems: New insights from an ecosystem nutrition perspective1. Issue 2 (26th February 2016) - Lang, Friederike; Bauhus, Jürgen; Frossard, Emmanuel; George, Eckhard; Kaiser, Klaus; Kaupenjohann, Martin; Krüger, Jaane; Matzner, Egbert; Polle, Andrea; Prietzel, Jörg; Rennenberg, Heinz; Wellbrock, Nicole
Abstract: Phosphorus is one of the major limiting factors of primary productivity in terrestrial ecosystems and, thus, the P demand of plants might be among the most important drivers of soil and ecosystem development. The P cycling in forest ecosystems seems an ideal example to illustrate the concept of ecosystem nutrition. Ecosystem nutrition combines and extents the traditional concepts of nutrient cycling and ecosystem ecology. The major extension is to consider also the loading and unloading of nutrient cycles and the impact of nutrient acquiring and recycling processes on overall ecosystem properties. Ecosystem nutrition aims to integrate nutrient related aspects at different scales and in different ecosystem compartments including all processes, interactions and feedbacks associated with the nutrition of an ecosystem. We review numerous previous studies dealing with P nutrition from this ecosystem nutrition perspective. The available information contributes to the description of basic ecosystem characteristics such as emergence, hierarchy, and robustness. In result, we were able to refine Odum's hypothesis on P nutrition strategies along ecosystem succession to substrate related ecosystem nutrition and development. We hypothesize that at sites rich in mineral‐bound P, plant and microbial communities tend to introduce P from primary minerals into the biogeochemical P cycle (acquiring systems), and hence the tightness of the P cycle is of minor relevance for ecosystem functioning. In contrast, tight P recycling is a crucial emergent property of forest ecosystems established at sites poor in mineral bound P (recycling systems). We conclude that the integration of knowledge on nutrient cycling, soil science, and ecosystem ecology into holistic ecosystem nutrition will provide an entirely new view on soil–plant–microbe interactions.